2020
DOI: 10.1017/s095834402000004x
|View full text |Cite
|
Sign up to set email alerts
|

The monolingual problem of computer-assisted language learning

Abstract: This paper sets out to discuss the monolingual problem within computer-assisted language learning (CALL) research and CALL product development, namely a lack of knowledge about how CALL products and projects can support learners in using all their linguistic resources to achieve language-learning- and language-using-related goals, and a lack of CALL products and projects that realize this potential, or that support specific plurilingual skill development. It uses an analysis of CALL-related papers to demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In response to the research question, the study observed a long list of challenges in using VR environment to improve receptive and productive skills. Despite these challenges, VR as an emerging and promising educational technology can potentially overcome instructional challenges by conducting further research to overcome them (Buendgens-Kosten, 2020; Gillespie, 2020). The abovementioned reported challenges serve as a reminder to researchers about problems ahead of the field and the need to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the research question, the study observed a long list of challenges in using VR environment to improve receptive and productive skills. Despite these challenges, VR as an emerging and promising educational technology can potentially overcome instructional challenges by conducting further research to overcome them (Buendgens-Kosten, 2020; Gillespie, 2020). The abovementioned reported challenges serve as a reminder to researchers about problems ahead of the field and the need to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This feature fosters knowledge sharing and community building (Cochrane, 2016) and creates personally meaningful moments that facilitate learning process (Hu-Au and Lee, 2017). This environment goes beyond copying reality and provides a sociolinguistics-informed environment that develops language learners’ understanding and knowledge of multilingual culture (Buendgens-Kosten, 2020; Gillespie, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In language education, the popularity of English education in China is getting higher and higher, and the traditional language education methods are difficult to meet people's needs [1]. In this context, Computer Assisted Language Learning (CALL) has become a research hotspot [2]. CALL system not only is used in online education, but also includes English education platforms such as text, image, audio, and video, which also play an important role on the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…e rst generation of computer-assisted instruction systems was introduced by IBM in the United States in 1946, more than ten years after the development of the rst computer [2][3][4]. Because the system was large and inconvenient at the time, it was not widely popularized or used.…”
Section: Introductionmentioning
confidence: 99%